Meningkatkan Pengetahuan Masyarakat tentang Pencegahan Penularan TBC di Pemukiman Padat Penduduk Kecamatan Medan Tuntungan - Hapsah Hapsah (Medan Resource Center, 2026)
Tuberculosis (TB) remains a major public health challenge in Indonesia, particularly in densely populated residential areas. This study aimed to enhance community knowledge regarding TB transmission prevention in Medan Tuntungan District. A quantitative method with a one-group pretest-posttest design was employed, involving 14 primary caregivers. The intervention consisted of the PAGAR BESI mentoring program, incorporating lectures, discussions, and leaflet-based media. The findings revealed a substantial increase in the proportion of participants with good knowledge, rising from 48% to 86% post-intervention. This improvement was attributed to the participatory approach and active family engagement. The study concludes that while health education effectively boosts knowledge, it must be complemented by physical environmental enhancements and the management of behavioral risk factors to comprehensively and sustainably interrupt the TB transmission chain.